Design Of Gas Leak Detection Using Gas Sensor And Microcontroller Based On Android - Indriyono, Bonifacius Vicky; Zahari, Iqlima; Karmila, Karmila; Alimudin, Erna; Wijoyo, Tomsen (Universitas Dian Nuswantoro and IndoCEISS, 2023)
Today the use of gas cylinders is increasingly widespread in society. Starting from simple stalls, street vendors and many households use these gas cylinders. The impact that occurs is an increase in orders to producers to produce gas cylinders. With the increase in orders, it causes less attention to the safety side of gas cylinders. One side of security that is not given enough attention is gas leaks. This study aims to implement Internet of Things (IOT) concept by designing a tool that can be used to detect leaks using the MQ-2 gas sensor and android. This tool serves to provide leak notifications in the form of an alarm. The alarm will turn on automatically when the sensor detects gas that emits an odor so that it can be anticipated immediately. The test results show that this detector can work properly and optimally in giving gas cylinder leak warnings.